The correlation between the distribution of tourism assets and the location of tourist accommodation in Łódź Province - Żakowska, Sylwia; Podhorodecka, Katarzyna (Turyzm/Tourism, 2018)
This article presents the correlation between natural and non-natural tourism assets and the distribution of tourist accommodation in the 24 powiats (districts) of Łódź Province. The authors, having divided these assets into natural and non-natural, discusses their occurrence in individual powiats. Next, tourist accommodation in Łódź Province is described, along with a presentation of statistical data. An important part of the paper is the presentation of the research results obtained by means of the point bonitation method. At the final stage, Spearman rank correlation coefficients is calculated, showing the strength of the relationship between selected tourism assets and the distribution of tourist accommodation.